Maternal urinary iodine concentration in pregnancy and children's cognition: results from a population-based birth cohort in an iodine-sufficient area. Issue 6 (12th June 2014) - Ghassabian, Akhgar; Steenweg-de Graaff, Jolien; Peeters, Robin P; Ross, H Alec; Jaddoe, Vincent W; Hofman, Albert; Verhulst, Frank C; White, Tonya; Tiemeier, Henning
Abstract : Objective: Reports from populations with an insufficient iodine intake suggest that children of mothers with mild iodine deficiency during pregnancy are at risk for cognitive impairments. However, it is unknown whether, even in iodine-sufficient areas, low levels of iodine intake occur that influence cognitive development in the offspring. This study investigated the association between maternal low urinary iodine concentration (UIC) in pregnancy and children's cognition in a population-based sample from a country with an optimal iodine status (the Netherlands). Setting and participants: In 1525 mother–child pairs in a Dutch multiethnic birth cohort, we investigated the relation between maternal UIC<150 μg/g creatinine, assessed <18 weeks gestation and children's cognition. Outcomes measures: Non-verbal IQ and language comprehension were assessed during a visit to the research centre using Dutch test batteries when the children were 6 years. Results: In total, 188 (12.3%) pregnant women had UIC<150 μg/g creatinine, with a median UIC equal to 119.3 μg/g creatinine. The median UIC in the group with UIC>150 μg/g creatinine was 322.9 μg/g and in the whole sample 296.5 μg/g creatinine. There was a univariate association between maternal low UIC and children's suboptimum non-verbal IQ (unadjusted OR=1.44, 95% CI 1.02 to 2.02). However, after adjustment for confounders, maternal low UIC was not associated with children's non-verbal IQ (adjusted OR=1.33, 95% CI 0.92 to 1.93). There was no relation between maternal UIC in early pregnancy and children's language comprehension at 6 years. Conclusions: The lack of a clear association between maternal low UIC and children's cognition probably reflects that low levels of iodine were not frequent and severe enough to affect neurodevelopment. This may result from the Dutch iodine fortification policy, which allows iodised salt to be added to almost all processed food and emphasises the monitoring of iodine intake in the population.